Conductance in Discrete Dynamical Systems - Fernandes, Sara (2012)
We will cover results related to the study of the conductance on digraphs arising from discrete dynamical systems. Several definitions of conductance are known and we present a study which gives a comparison between them in order to choose the appropriate definition to applications. The study makes a strong use of symbolic dynamics. As an application, we analyze the mechanical system of the nonlinear pendulum.